Comparing the effect of Alpha blocker (Silodosin) and Phosphodiesterase type 5 inhibitor (Tadalafil) in benign prostate hyperplasia patients with lower urinary tract symptoms: a single centre study - Narayan Singh, Sanket; Biswas, Manoj; Mittal, Ankur; Kalra, Yogesh; Sarpal, Rajeev; Agrawal, Shikhar; Pal, Ravinder; Chugh, Bhavishya (International Surgery Journal, 2018)
Background: Benign prostatic hyperplasia (BPH) is a histologic diagnosis that refers to the proliferation of smooth muscle and epithelial cells within the prostatic transition zone. The aim of this systematic review is to determine the comparative effectiveness and safety of phosphodiesterase 5 inhibitors (PDE5-Is) and alpha blockers used alone or in combination for the treatment of lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH). Methods: We analyzed 54 patients of BPH with LUTS with baseline IPSS, Qmax and PVR over one-year period. They were randomized equally in three groups i.e. group receiving alpha blocker, group receiving phosphodiesterase 5 inhibitors and group receiving combination of the two drugs. These patients were followed up at the end of 1st month and 3rd month and IPSS, Qmax and PVR was compared. Results: Out of 54, 45 patients completed the study. At the end of the study all the three groups showed significant improvement in IPSS, PVR and Qmax, all p <0.05, but the combination group showed much better improvement in terms of percentage. Two patients on alpha blockers had episode of hypotension. Conclusions:Thus, we summarize that phosphodiesterase 5 inhibitors should be preferred over alpha blockers in patients with LUTS/BPH as it has, firstly, outcome similar to alpha blockers. Secondly, have no documented side effect. Third, can be given in any patient, irrespective of the fact that whether the patient is suffering from erectile dysfunction or not.